Assessing the Effects of Crowding Perception and Gender Among Southeast Asia Pilgrims in Mina, Saudi Arabia - Alsolami, B; R. Embi, M; A. Majrashi, A; S. Karban, A (International Journal of Engineering and Technology, 2018)
This study gives a better understanding of the effect of crowding on pilgrims at the Hajj. It explores the levels of perceived crowding of Southeastern Asian pilgrims and investigates the effects of gender on their perceived crowding. Questionnaire in both Bahasa Melayu and English languages were administered for data collections from randomly selected pilgrims, (n=128), from the Southeast Asia Hajj group at Mina for three days (10th, 11th and 12th of Dhul-Hijjah). Results revealed that pilgrims witness high levels of crowd perception within their stay at Mina. In addition also, differences between the overall perceived crowding, perceived human crowding and perceived spatial crowding among pilgrims were revealed. Perceived human crowding was found as an indicator to the overall perceived crowding at Mina.Â  Future research could be carried out to assess the effects of other factors such as education and cultural backgrounds and these findings can help authorities in charge of formulating policies manage crowd levels and perception.Â Â